Rama revealed - Clarke, Arthur C. (Arthur Charles), 1917-2008; Lee, Gentry (Bantam spectra book., 1994)
Nicole Wakefield, ex-governor of the colony of humans on the spaceship Rama III, is in her cell awaiting death for treason. She opposed the colony's new rulers. But Richard, her husband whom she thought dead, sends robots to rescue her.